2016
DOI: 10.1002/j.0022-0337.2016.80.3.tb06091.x
|View full text |Cite
|
Sign up to set email alerts
|

Test‐Enhanced Learning in Competence‐Based Predoctoral Orthodontics: A Four‐Year Study

Abstract: Dental educators intend to promote integration of knowledge, skills, and values toward professional competence. Studies report that retrieval, in the form of testing, results in better learning with retention than traditional studying. The aim of this study was to evaluate test-enhanced experiences on demonstrations of competence in diagnosis and management of malocclusion and skeletal problems. The study participants were all third-year dental students (2011 N=88, 2012 N=74, 2013 N=91, 2014 N=85) at New Yor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Spaced learning was also implemented in simulation settings (n = 24, 23%), generally used to disperse training sessions over time to stimulate clinical skill acquisition. In total 24 studies (23%) were conducted in classrooms and applied to various educational activities, ranging from repeated practice and testing of basic science mechanisms, to clinical scenarios and skill training.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Spaced learning was also implemented in simulation settings (n = 24, 23%), generally used to disperse training sessions over time to stimulate clinical skill acquisition. In total 24 studies (23%) were conducted in classrooms and applied to various educational activities, ranging from repeated practice and testing of basic science mechanisms, to clinical scenarios and skill training.…”
Section: Resultssupporting
confidence: 65%
“…Almost half of the empirical research articles (n = 48, 47%) did not explicitly mention a theoretical framework. In total, nine theoretical frameworks were mentioned in the remaining studies of which the Spacing effect (n = 40) and Testing effect (n = 31) were named most often. Other frameworks were Cognitive Load Theory (n = 4), Desirable Difficulties Theory (n = 2), Retrieval hypothesis (n = 2), Total‐time hypothesis (n = 2), Learning Theory (n = 1), Metacognitive Theory (n = 1) and Kolb's Experiential Learning Theory (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Although prior studies have suggested that test‐enhanced learning improves recall and may improve performance in summative competency assessments, 3 , 4 there may be undesirable side effects on students’ perceptions of instruction 13 . Through assessments, learners are made aware of errors, and this knowledge may threaten self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a test‐enhanced method of instruction based on formative assessments with feedback was introduced. When compared to a traditional classroom approach (presentations and in‐class exercises), the test‐enhanced method generally boosted performance (i.e., higher grades), while not demonstrably affecting pass rates 3 . Although test‐enhanced methods (in areas not related to competency‐based dental education) have been reported to improve performance, they also deflate students’ confidence compared to traditional studying 4 , 5 .…”
mentioning
confidence: 93%
See 1 more Smart Citation